Philosophy within its proper bounds - Machery, Edouard (Oxford University Press, 2017)
Edouard Machery argues that resolving many traditional and contemporary philosophical issues is beyond our epistemic reach and that philosophy should re-orient itself toward more humble, but ultimately more important intellectual endeavours. Any resolution to many of these contemporary issues would require an epistemic access to metaphysical possibilities and necessities, which, Machery argues, we do not have. In effect, then, this work defends a form of modal skepticism. It assesses the main philosophical method for acquiring the modal knowledge that the resolution of modally immodest philosophical issues turns on: the method of cases, that is, the consideration of actual or hypothetical situations (which cases or thought experiments describe) in order to determine what facts hold in these situations